Social Empowerment through Santalwomen Education: A Comparative Study on Birbhum, West Bengal (International Journal of Emerging Trends in Science and Technology, 2017)
Education is one of the most important tools of empowering Santal women. This paper analyse thecurrent educational status of Santal women and role of education in social empowering of Santal womenat Birbhum,West Bengal. Present paper compared the empowering status among the Santal Women atPatharghata, Bergram and Ballipara of Birbhum, West Bengal.